(untitled) (International Seven Journal of Multidisciplinary, 2023)
Introduction: The practice of handball faces many challenges of gender inequality, physical activity, including team sports, has an impact on quality of life and the pursuit of sporting excellence involves several factors and is a complex process, quality of life is affected by changes in health status. Women faced challenges in practicing sports in the 19th century, with gender stereotypes associated with men. Objective: To identify the influence of the sport of handball on the quality of life of recreational and performance women. Method: This integrative literature review included a search for articles in databases such as PUBMED, SCIELO and Google Scholar, using the descriptors in Health Sciences (Decs): Quality of life, sports performance, elite athletes and female athletes. Results: Initially, 3,209 articles were identified and analyzed, and the selection was refined to 18 articles related to the proposed theme and approach to women’s quality of life in the context of handball, both recreational and performance. Conclusion: This review provided a comprehensive understanding of the influence of handball on women’s quality of life, considering different contexts of practice, motivational factors and consequences for physical and emotional well-being, despite small recurring unforeseen events related to the career of performance athletes, showing a direct relationship more positively when related to the recreational aspect, while the performance aspect showed positive relationships, but the negative ones are more prominent.